Onde a confiança bate o martelo: histórias e disputas no mercado brasileiro de leilões - Pereira, Luiz Gustavo Simão (Universidade Federal de São Carlos, 2024)
Auctions constitute a vast market in contemporary Brazil, particularly concerning the trade of used vehicles. These dynamic spaces constitute lucrative and contested terrains, serving as essential hubs for the sale, distribution, and consumption of used cars across the country, with São Paulo standing as a prominent example. While analyses of auctions often lean towards economic dimensions, the political, social, and cultural underpinnings of these markets remain largely unexplored. This dissertation seeks to unravel the fundamental principles shaping the Brazilian auction market and how they emerge, stabilize, and undergo a transformation through interactions with various market stakeholders. To accomplish this, I draw upon a diverse array of sources: conducting interviews with auctioneers personally or accessing them through online platforms, examining legal documents governing the profession at the national level – including decrees and laws – and gathering, organizing, and analyzing sector-related news disseminated through promotional materials, as well as in print and digital newspapers. Through this comprehensive approach, I contend that the bedrock of this substantial market in contemporary Brazil lies in the cultivation of trust. However, this trust is not inherent or preordained; rather, it is meticulously constructed through a myriad of interactions – be they disputes, alliances, or negotiations – that auctioneers engage in amongst themselves, with legislators, and with their clientele.
Where trust strikes the hammer: stories and disputes in the brazilian auction market
Keywords: Confiança; Leilões; Elites; Veículos; Trust; Auctions; Elites; Vehicles; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS